UJI EFEKTIVITAS EKSTRAK DAUN TALAS BENENG (Xanthosoma Undipes K.Koch) SEBAGAI PENGENDALI JAMUR Fusarium oxysporum PADA TANAMAN PISANG SECARA IN VITRO - Andi Apriany Fatmawaty; Nuniek Hermita; Martina Nursaprudianti; Julio Eiffelt R Rumbiak; Dewi Hastuti (Jurnal Agroekoteknologi, 2020)
Fusarium is a phatogenic fungy that causes wilting in banana plants. One of alternative in controlling Fusarium oxysporum fungy is by using Botanical Pestiside on of them is talas beneng. This plants is local plants that grows wild around Karang Mountain, Pandeglang, Banten. A research to determine the effectiviness extract of talas beneng leaf (Xanthosoma undipes K.Koch) as fungy control Fusarium oxysporum in banana plants in vitro. The research used  randomized completely design with five treatments and five replication. The treatments is consisting of talas beneng leaf extract 0%, 5%, 5,5%, 6%, dan 6,5%. Observation was conducted after incubation for nine days at room temperature. The parameters observed was inhibition Fusarium oxysporum growth with indicated size of the diameter mycelium colony, inhibition percentage of mycelium and inhibits and thickness mycelium . The result of the talas beneng leaf extract showed that there was no difference in the concentration of the talas beneng leaf extract on the diameter of mycelium Fusarium oxysporum, but the extract of talas beneng leaf effective for inhibits and thickness myscelium density in mycelium fungi in vitro with concentration is 6%.